Hope and asylum everyday life, precarity and social change - Elsrud, Torun; Lalander, Philip 1965-; Andreasson, Jesper; Herz, Marcus (Routledge, 2025)
This book applies perspectives of hope to understand the precariousness, suffering, and agency of people seeking asylum. With attention to the restrictions and austerity politics that have characterised public policy following the significant rise in asylum applications in 2015, it draws on longitudinal ethnographic fieldwork in the Swedish asylum context, together with data collected in other European countries, to explore how the circumstances of those navigating asylum processes evolve and connect to their notions of hope and the future. Departing from the ambiguities and fragility surrounding hope in the asylum context, Hope and Asylum analyses people’s lived experiences and their navigation of uncertainty and precariousness during the migration process. While hope can provide individuals with support and empowerment, it can also cause pain and be exploited by authorities to control and disempower. The book argues that critically scrutinising current asylum regimes and exposing the enduring emotional and embodied scars they inflict through the bureaucratic violence of welfare states is essential for mobilising efforts toward social justice and human rights. Demonstrating the importance of hope and related concepts to our understanding of daily life experiences, social interaction, and precariousness within the asylum context, it will appeal to scholars across the social sciences with interests in migration and diaspora, immigration policy, refugee studies, and asylum regimes.